The Insurance Industry in a Climate of Change - Hanson, Philip B H (2011)
For industries that operate and rely on risk, such as insurance, climate change is a dynamic issue that requires a multi-faceted business response. Insurance companies are not only changing their risk management approaches but also seeking opportunities associated with changes in weather. This study looks at the fundamental drivers and barriers of a proactive approach to climate change for the insurance industry with particular focus on the role of key stakeholders. In order to give the findings a greater contextual grounding the opportunities and costs as well as relative responses across the industry are examined. Key findings suggest societal norms play a significant role in driving insurers to take action while gaps in governance create a fundamental barrier.